Phenotype 2 Familial Mediterranean Fever: Evaluation of 22 Case Series and Review of the Literature on Phenotype 2 FMF. (March 2013) - Altunoğlu, Alpaslan; Erten, Şükran; Canoz, Mujdat Batur; Yuksel, Aydan; Ceylan, Gulay Gulec; Balci, Serdar; Dogan, Hayriye Tatli
<x xml:space="preserve">Abstract</x> Familial Mediterranean fever (FMF) is an autosomal recessive autoimmune disorder characterized by recurrent bouts of fever and serosal inflammation. FMF may be complicated by AA-type amyloidosis, worsening the prognosis, with associated renal failure in some patients. Complication rate varies with race, being as high as 60% in Turks and as low as 2% in Armenians. In a few cases of patients with FMF (phenotype 2), amyloid nephropathy may be the presenting manifestation. This study included 420 patients who were admitted to the Nephrology and Rheumatology Departments of Atatürk Education and Research Hospital with unexplained proteinuria/nephrotic syndrome. The initial screening test for amyloidosis was the presence of significant proteinuria (300 mg/24 h). All MEFV gene exons were screened for causative mutations by direct DNA sequencing to check for any mutations. There were 22 phenotype 2 FMF patients with 27 allelic variants. The most prevalent allelic variants were M694V (10/27, 37%) and E148Q (7/27, 26%). Phenotype 2 FMF is not as rare as it was thought before; this should be kept in mind for all patients with unexplained proteinuria and/or acute phase response in high-risk ethnic groups for FMF.